PENGEMBANGAN MEDIA GAME EDUCATION DALAM PEMBELAJARAN TEMATIK TERPADU BERBASIS ADOBE ANIMATE CC DI KELAS II SEKOLAH DASAR - Husni Wulandari; Risda Amini (KOLONI, 2022)
This research was motivated by the game education which was developed in previous studies, only specifically on one learning content. There are still few who develop it as an integrated thematic learning media. In this study, researchers developed education game adobe animate cc as an integrated thematic learning media in grade II Elementary School so that it can be used in the learning process in the 2013 curriculum. Therefore, the game education media based on adobe animate cc tested in the field to determine the validity and practicality of the media. This research is a Research & Development research. The development model used is the ADDIE model. With the stages of Analysis (Analysis), Design (Design), Development (Development), Implementation (Implementation) and Evaluation (Evaluation). Collecting data using validation sheets by validators and teacher response questionnaires. The trial subjects in this study were 10 students of class II SDI Sjech Djamil Djambek. The results of this study obtained a media game education on integrated thematic learning based on Adobe Animate cc in grade II Elementary School. The results of the overall validity test of the game education by three validators obtained an average value of 91.67% with very valid criteria. The results of the practicality test of game education by the teacher obtained a value of 95.38% with very practical criteria. Based on the results of the research that has been done, it can be concluded that the game education media as an integrated thematic learning media based on Adobe Animate cc in Grade II Elementary School is valid and practical to use in the integrated thematic learning process in Grade II Elementary School.  Keywords: Media Game Education, Thematic, Adobe Animate CC, ADDIE